Potential impact of autoimmune diseases family history in IgG4-related disease: a retrospective cohort study - Wen Zhang; Xiaofeng Zeng; Zheng Liu; Yunyun Fei; Jieqiong Li; Yu Peng; Hui Lu; Jingna Li; Ruijie Sun; Yuxue Nie; Linyi Peng; Jiaxin Zhou (RMD Open, 2023)
Objective Autoimmune comorbidities may be associated with IgG4-related disease (IgG4-RD), here we aimed to determine the correlation of autoimmune diseases (AID) family history and IgG4-RD in a Chinese cohort.Methods This retrospective cohort study identified 628 cases of IgG4-RD in Peking Union Medical College Hospital. Patients were classified into two groups, with AID family history group (AID-positive) and without AID family history group (AID-negative). We viewed the potential value of AID family history on IgG4-RD by comparing the differences between the two groups. In addition, Cox regression analysis estimated CIs and HR for IgG4-RD risk.Results 93 (14.8%) IgG4-RD patients had AID family history. Compared with AID-negative group, baseline data analysis revealed that AID-positive group patients had an earlier age of IgG4-RD onset (50.4±14.8 vs 54.2±12.6, p=0.014*), a higher percentage of antinuclear antibody (ANA) positivity (38.9% vs 22.7%, p=0.0277*) and Riedel thyroiditis (10.9% vs 2.4%, p=0.001*), were prone to comorbid with other AID (16.1% vs 6.2%, p=0.0238*). Cox analysis found that younger age (HR 0.97 (95% CI 0.94 to 0.99), p=0.0384*) and higher proportions of baseline peripheral eosinophils (HR 1.1 (95% CI 1.02 to 1.2), p=0.0199*) increased the risk of unfavourable prognosis for AID-positive IgG4-RD patients.Conclusions 14.8% of IgG4-RD patients had AID family history, with younger age of disease onset age and higher frequency of ANA positivity in AID-positive group, indicating that IgG4-RD may share genetic background with other AID.